IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hoelter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Doerfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Abstract Background rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4.5 hours after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on PCS are scarce. Methods Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. Patients were categorized into PCS or ACS, based on clinico-radiological findings. We analyzed hemorrhagic complications, clinical and imaging efficacy outcomes and mortality rates comparing PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results Of 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission (27 (22.0%) PCS and 96 (78.0%) ACS). The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower (8 (5-15) vs. 14 (9-18), p=0.005) and infarction visible on follow-up imaging was less common (70.4% vs. 87.5%, aRD -18.9% (-39.8% to -2.2%) in the PCS patient group. There was a trend towards a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS versus ACS without reaching statistical significance (5.3% vs. 16.9%, aRD -10.4% (-20.4% to 4.0%). The incidence of symptomatic ICH (according to ECASS III criteria: 2.6% vs. 3.5%, aRD -2.9% (-10.3% to 9.2%)), efficacy outcomes and mortality rates were similar in PCS and ACS patients. Conclusions In this real world clinical cohort, the safety and efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS with a trend towards less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 hours also in selected patients with PCS.